Correction to: Exposure to arsenic in utero is associated with various types of DNA damage and micronuclei in newborns: a birth cohort study - Panida Navasumrit; Krittinee Chaisatra; Jeerawan Promvijit; Varabhorn Parnlob; Somchamai Waraprasit; Chalida Chompoobut; Ta Thi Binh; Doan Ngoc Hai; Nguyen Duy Bao; Nguyen Khac Hai; Kyoung-Woong Kim; Leona D. Samson; et al. (BMC, 2019)
Following publication of the original article [1], the author reported that incorrect version of Tables 1, 3, 5 and 6 were published.